Firefly algorithm for path optimization in PCB holes drilling process - Mohd Muzafar, Ismail (IEEE Conference Publications, 2014)
Proceeding of The International Conference in Green and Ubiquitous Technology (GUT 2012) at Bandung, Indonesia on 7 July 2012 through 8 July 2012. Link to publisher's homepage at http://ezproxy.unimap.edu.my:2080/Xplore/dynhome.jsp